Implementing technology-based embedded assessment in the home and community life of individuals aging with disabilities: a participatory research and development study. - Chen, Ke-Yu; Harniss, Mark; Patel, Shwetak; Johnson, Kurt (Disability & Rehabilitation: Assistive Technology, 2014)
Purpose: The goal of the study was to investigate the accuracy, feasibility and acceptability of implementing an embedded assessment system in the homes of individuals aging with disabilities. Method: We developed and studied a location tracking system, UbiTrack, which can be used for both indoor and outdoor location sensing. The system was deployed in the homes of five participants with spinal cord injuries, muscular dystrophy, multiple sclerosis and late effects of polio. We collected sensor data throughout the deployment, conducted pre and post interviews and collected weekly diaries to measure ground truth. Results: The system was deployed successfully although there were challenges related to system installation and calibration. System accuracy ranged from 62% to 87% depending upon room configuration and number of wireless access points installed. In general, participants reported that the system was easy to use, did not require significant effort on their part and did not interfere with their daily lives. Conclusions: Embedded assessment has great potential as a mechanism to gather ongoing information about the health of individuals aging with disabilities; however, there are significant challenges to its implementation in real-world settings with people with disabilities that will need to be resolved before it can be practically implemented.